Messages : - DeVito, Joseph A. (Harper & Row, 1990)
Moving from the parent text, "Human Communication, 5th ed", this concise text introduces the essential skills and applications of interpersonal, small group and public speaking communication. Joseph DeVito takes beginners through the theoretical fundamentals of communication, including the self, perception and listening, and verbal and non-verbal messages. The book lays down the foundations for mastering the essential skills of communication